Insights From Veterinary Disciplinary Actions in California 2017–2019 - Labriola, Jake; Garabed, Rebecca; Sinclair, Carly; Marsh, Antoinette E. (Frontiers in Veterinary Science, 2021)
There is increasing concern within the veterinary medical community (veterinarians and veterinary students) that disgruntled clients are unfairly leveraging various legal tools against veterinarians. Clinical veterinarians and veterinary students should be aware of the most common types of problems arising within the clinic and how they can lead to formal consumer complaints. The study describes and categorizes with greater detail the types of violations or “causes for discipline” that occur, as well as specific sanctions imposed on veterinarians formally disciplined for standard of care-related violations between 2017 and 2019, for California. In addition, the study calculated the frequency of disciplinary actions and their basic summary statistics regarding the temporal aspect of how lawsuits typically unfold. Using public documents from California, the study describes the analysis and trends for the purpose of providing contextual evidence to inform and guide potential veterinary educational interventions. Although specific to California, this study can serve as a template methodology for comparisons to other states.